The Correlation Between Pre Operative Anxiety Levels and Post Operative Pain Intensity in Femoral Fracture Patients - Annas Tasya Permata Sari; Fahrun Nur Rosyid (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
The aim of this study was to examine the relationship between the levels of preoperative anxiety and the intensity of postoperative pain among patients with femur fractures undergoing treatment at Prof. Dr. R. Soeharso Orthopedic Hospital in Surakarta. The research design employed in this study was a cross-sectional study, and data were collected from 27 respondents using simple random sampling method. The results of this study showed that mild anxiety levels were present in 15 patients (55.6%), moderate anxiety in 10 patients (37.0%), and severe anxiety in 1 patient (3.7%). Moderate pain was reported by 15 patients (55.6%), while mild pain was reported by 8 patients (29.6%) and severe pain by 4 patients (14.8%). The statistical analysis revealed a noteworthy association between preoperative anxiety levels and postoperative pain intensity (p=0.023). In conclusion, pre operative anxiety levels are significantly associated with post operative pain intensity in patients with femur fractures